Induction Motor Performance During Voltage Dip - Abdul Aziz, Ahmad Farhan (Universiti Teknologi PETRONAS, 2016)
Power quality issue is one of the major concern in industrial power system. Voltage dip is one of the power quality problem which mainly caused by fault in the upstream section. Induction motor plays an important role in process plant which drive majority of the loads. It is important to maintain the performance of induction motor because sudden shutdown may lead to losses in term of product and economy. The focus of this paper is on the performance of induction motor during voltage dip including the analysis of several parameters. The experimental study will be carried out by using voltage dip simulator.